EFFECT OF ROSEMARY AROMATHERAPY (ROSMARINUS OFFICINALIS) TO MEMORY OF SHORT-TERM MEMORY IN ELDERLY - Sulung, Neila; Aulia, Fajri Febrini (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Aromatherapy is a way of healing by using the concentration of highly aromatic essential oils that was extracted from plants. The purpose of this research is to identify the effects the provision of aromaterapy rosemary to short-term memory elderly. The design of this research is Quasi Experiment Design and research design of One Group Pre-test Post-test and sampling technique using Purposive Sampling. The population in this study were all elderly in Elderly Social Institution Sabai Nan Aluih Sicincin with a sample of 16 people. Data were analyzed by using Paired T-Test with significant value α = 0,005. The results showed before giving rosemary aromatherapy average short-term memory of elderly is 24,31. The results after giving rosemary aromatherapy the average short-term memory of the elderly is 26.50. Bivariate results obtained p value 0,000. So it shows there is a significant difference of short-term elderly significant memory before and after giving aromatherapy to elderly. The influence aromatherapy rosemary can improve short-term memory in elderly. So that we hopes officer in the nursing home can collaborate with health worker specially nurses can increase their service to elderly, one of them is to apply non-pharmacological treatment to increase memory.